Left atrial unloading with an 8 mm septal cutting balloon to treat postcapillary pulmonary hypertension: a case report. (11th November 2021) - Bauer, Fabrice; Besnier, Emmanuel; Aludaat, Chadi; Breil, Romain; Bettinger, Nicolas; Fauvel, Charles; Wurtz, Véronique; Raitiere, Olivier; Si Belkacem, Nassima; Bouhzam, Najime
Abstract: We report the case of a 58‐year‐old female with severe postcapillary pulmonary hypertension (averaged mean pulmonary arterial pressure was 49 mmHg, pulmonary arterial wedge pressure 29 mmHg, and right atrial pressure 8 mmHg) due to heart failure with preserved ejection fraction. A left‐to‐right atrial shunt was created using an 8 mm cutting balloon, under transesophageal echocardiography guidance. Both pulmonary arterial and wedge pressure dramatically decreased after the procedure. Symptoms immediately improved and benefits were sustained at 6 months of follow‐up. This case suggests that iatrogenic septal defect using a cutting balloon could be an option to treat symptomatic postcapillary pulmonary hypertension.